DAMPAK PERNIKAHAN DINI TERHADAP KEHARMONISAN KELUARGA DAN POLA ASUH ANAK (Studi Kasus Atas Masyarakat Desa Sukaraja Lampung Timur) - Heri Cahyono; Eka Dewi (AT-TAJDID, 2018)
Early marriage affects the formation of a family that is not harmonious. That is because psychologically and socio-economically the early marriage partner is not yet mature. They are classified as unstable and generally do not have a permanent job. Besides being unstable, early marriage partners also do not have much knowledge about how to care for children, so they cannot apply the right pattern of parenting.The hypothesis in this study is that there is the effect of early marriage on Family Harmony in the village of Sukaraja Tiga, Kec. Marga Tiga, Kab. East Lampung and there is an influence of early marriage on the pattern of child care in the village of Sukaraja Tiga, Kec. Marga Tiga, Kab. East Lampung. This study is a population study with a population of 15 early marriage partners. Data analysis in this study uses the Product Moment formula.The results showed that the first hypothesis was accepted, as evidenced by the price of r_xy 0.573 greater than r_tabel at df = N-nr = 15-2 = 13 and a significance level of 5% at 0.514, so it can be concluded that the theory that "marriage at the age young people will invite many unexpected problems because their psychological aspects are immature. It is not uncommon for couples who experience a collapse in a household due to a marriage that is too young "to be proven correct.The second hypothesis is also accepted, as evidenced by the price of r_xy 0.532 greater than r_tabel at df = N - nr = 15-2 = 13 and at the 5% significance level of 0.514 so it can be concluded the theory states that "Age is one of the characteristics of maturity where it can affect its role in children, because with increasing age a person occurs the process of maturity of both the organ and the way of his mind so that it can provide the right parenting for his child "proved correct.